A theoretical model of hyperbranched polymerization involving an ABf monomer. Part 2, The average polymerization degree and dispersity index - Galina, H.; Walczak, M. (Polimery, 2022)
A generalized theoretical model of hyperbranched polymerization of an ABf monomer was used to calculate the weight average polymerization degree (Pw) and dispersity index (DM) of the resulting hyperbranched polymers. The monomer functionalities were f = 2, 4, or 6. The model derived in Part I of the series and based on the Smoluchowski coagulation equation was used. The monomer functional groups B reacted according to the first shell substitution effect principle. Both, the weight average polymerization degree and dispersity index were found to grow with conversion the faster, the higher was the monomer functionality and the more positive was the substitution effect.